(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article describes the history of the translation of one of unique works of the famous Russian writer L.N. Tolstoy. The author also raises the questions of when and how it was translated. The article analyzes translation skills of M. Auezov who managed to convey the artistry of the work «After the Ball». M. Auezov’s translation is an excellent example of free interpretation. In the article the author reflects on the identity and distinctions of the original and its translation, defines the missed episodes in free interpretation, illustrates transformations of compound sentences into simple sentences with examples. Special attention is given to sentences skillfully translated by Auezov. In the final part it is noted that in general this translation can be considered to be very successful.